A thermo-responsive alginate nanogel platform co-loaded with gold nanoparticles and cisplatin for combined cancer chemo-photothermal therapy. (May 2019) - Mirrahimi, Mehri; Abed, Ziaeddin; Beik, Jaber; Shiri, Isaac; Shiralizadeh Dezfuli, Amin; Mahabadi, Vahid Pirhajati; Kamran Kamrava, S.; Ghaznavi, Habib; Shakeri-Zadeh, Ali
Graphical abstract: A newly developed thermo-sensitive nanogel platform for combined cancer chemo-photothermal therapy Abstract: The current interest in cancer research is being shifted from individual therapy to combinatorial therapy. In this contribution, a novel multifunctional nanoplatform comprising alginate nanogel co-loaded with cisplatin and gold nanoparticles (AuNPs) has been firstly developed to combine photothermal therapy and chemotherapy. The antitumor efficacy of the as-prepared nanocomplex was tested against CT26 colorectal tumor model. The nanocomplex showed an improved chemotherapy efficacy than free cisplatin and caused a significantly higher tumor inhibition rate. The in vivo thermometry results indicated that the tumors treated with the nanocomplex had faster temperature rise rate under 532 nm laser irradiation and received dramatically higher thermal doses due to optical absorption properties of AuNPs. The combined action of chemo-photothermal therapy using the nanocomplex dramatically suppressed tumor growth up to 95% of control and markedly prolonged the animal survival rate. Moreover, tumor metabolism was quantified by [ 18 F]FDG (2-deoxy-2-[ 18 F]fluoro-D-glucose)-positron emission tomography (PET) imaging and revealed that the combination of the nanocomplex and laser irradiation have the potential to eradicate microscopic residual tumor to prevent cancer relapse. Therefore, the nanocomplex can afford a potent anticancer efficacy whereby heat and drug can be effectively deliver to the tumor, and at the same time the high dose-associated side effects due to the separate application of chemotherapy and thermal therapy could be potentially reduced.